Cover Feature: Coordination‐Cage‐Catalysed Hydrolysis of Organophosphates: Cavity‐ or Surface‐Based? (Chem. Eur. J. 14/2020). Issue 14 (6th February 2020) - Taylor, Christopher G. P.; Metherell, Alexander J.; Argent, Stephen P.; Ashour, Fatma M.; Williams, Nicholas H.; Ward, Michael D.
Abstract : The cavities of coordination cages are well known to be able to bind small‐molecule guests and, in some cases, catalyse reactions on bound guests. But it is not always appreciated that catalytic reactivity can be associated with the external surface of coordination cages, as well as the interior cavity. In this article Ward and co‐workers report how a series of phospho‐triesters, including some toxic insecticides, undergo cage‐catalysed hydrolysis, but at the cage exterior surface, even though some of them do bind inside the cavity. More information can be found in the Full Paper by N. H. Williams, M. D. Ward et al. on page 3065 .